2010
DOI: 10.5395/jkacd.2010.35.6.429
|View full text |Cite
|
Sign up to set email alerts
|

Study of endodontic working length of Korean posterior teeth

Abstract: Objectives:The aim of this study was to investigate average working lengths of Korean posterior teeth and evaluate validity of endodontic file length. Materials and Methods:The endodontic working length of the posterior teeth of 670 Korean patients were measured than each mean value and standard deviation were investigated than the frequency deviation and standard deviation per each length were calculated. Results: Among the canals of premolar, 66.5% of canal length was marked under 20 mm by endodontic working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Currently, there are three standard lengths available for endodontic files: 21 mm, 25 mm, and 31 mm. In addition, various studies have been conducted to improve the intraoral accessibility of instruments for endodontic treatment [27]. Thus, modified endodontic files and obturation techniques have been developed (Pace et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are three standard lengths available for endodontic files: 21 mm, 25 mm, and 31 mm. In addition, various studies have been conducted to improve the intraoral accessibility of instruments for endodontic treatment [27]. Thus, modified endodontic files and obturation techniques have been developed (Pace et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Three standard lengths are available as 21 mm, 25 mm, and 31 mm, these lengths usually meet the majority of endodontic cases .The studies showed that there are differences in root canal lengths among populations. It has been found that the tooth lengths in Asians were shorter than Caucasians (Kim E et al 2005), and there was the difference in root canal lengths between Asians and western population with the latter having longer teeth (Kim J et al 2010). Variation in size, form and morphology of the teeth resulted in anomalies such as macrodontia, microdontia , hyperdontia, hypodontia, taurodontism and dens in dente.…”
Section: Discussionmentioning
confidence: 99%